All-fiber gain-switched laser at 2.8 μm - CHEN Hanbo; WANG Tao; GUO Chunyu; RUAN Shuangchen (Shenzhen Daxue xuebao. Ligong ban)
The mid-infrared pulsed lasers at 2.8 μm are widely used in scientific and biomedical fields. By cascading gain-switches, a 2.8 μm all-fiber gain-switched laser was achieved. The pump and oscillator are respectively a homemade 976 nm high power pulsed laser based on gain-switched and a Er3+∶ZBLAN (ZrF4-BaF2-LaF3-AlF3-NaF) fiber linear cavity with a pair of fiber Bragg gratings at both ends. The repetition frequency of the output pulses is 50 kHz, and the pulse width is 1.27 μs. The maximum output power is 175.2 mW, corresponding to pulse energy of 3.54 μJ. Owing to the high output stability of the 976 nm pump source based on gain-switched and optical amplifier, the 2.8 μm gain-switched laser is able to obtain more stable pulses than those achieved by the traditional pump source. This work not only enriches the researches on 2.8 μm all-fiber gain-switched lasers in terms of improving output characteristics, but also provides a scheme for gain-switched lasers at other bands to obtain more stable pulses.